Expression and Characterization of Streptococcal rgp Genes Required for Rhamnan Synthesis in Escherichia coli - Shibata, Yukie (American Society for Microbiology, 2002)
Six genes (rgpA through rgpF) that were involved in assembling the rhamnose-glucose polysaccharide (RGP) in Streptococcus mutans were previously identified (Y. Yamashita, Y. Tsukioka, K. Tomihisa, Y. Nakano, and T. Koga, J. Bacteriol. 180:5803-5807, 1998). The group-specific antigens of Lancefield group A, C, and E streptococci and the polysaccharide antigen of Streptococcus sobrinus have the same rhamnan backbone as the RGP of S. mutans. Escherichia coli harboring plasmid pRGP1 containing all six rgp genes did not synthesize complete RGP. However, E. coli carrying a plasmid with all of the rgp genes except for rgpE synthesized the rhamnan backbone of RGP without glucose side chains, suggesting that in addition to rgpE, another gene is required for glucose side-chain formation. Synthesis of the rhamnan backbone in E. coli required the initiation of transfer of N-acetylglucosamine to a lipid carrier and the expression of the rgpC and rgpD genes encoding the putative ABC transporter specific for RGP. The similarities in RGP synthesis between E. coli and S. mutans suggest common pathways for rhamnan synthesis. Therefore, we evaluated the rhamnosyl polymerization process in E. coli by high-resolution sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the lipooligosaccharide (LOS). An E. coli transformant harboring rgpA produced the LOS modified by the addition of a single rhamnose residue. Furthermore, the rgpA, rgpB, and rgpF genes of pRGP1 were independently mutated by an internal deletion, and the LOS chemotypes of their transformants were examined. The transformant with an rgpA deletion showed the same LOS profile as E. coli without a plasmid. The transformant with an rgpB deletion showed the same LOS profile as E. coli harboring rgpA alone. The transformant with an rgpF deletion showed the LOS band with the most retarded migration. On the basis of these results, we speculated that RgpA, RgpB, and RgpF, in that order, function in rhamnan polymerization.